Political connectedness and firm performance: Evidence from Germany - Alexandra Niessen; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2009)
This paper investigates politically connected firms in Germany. With the introduction of a new transparency law in 2007, information on additional income sources for all members of the German parliament became publicly available. We find that members of the conservative party (CDU/CSU) and the liberal party (FDP) are more likely to work for firms than members of left-wing parties (SPD and The Left) or the green party (Alliance 90/The Greens). Politically connected firms are larger, less risky, and have lower market valuations than unconnected firms. They also have fewer growth opportunities, but slightly better accounting performance. On the stock market, connected firms significantly outperform unconnected firms in 2006, i.e. prior to the publication of the data on political connections. Differences in stock market performance are much smaller in 2007.
Keywords: G14; G18; G30; G38; H89; K29; L14; 330; Political Connectedness; Firm Value; Firm Performance